Simplified procedure for laterally loaded drilled shafts in spatially random clays. Issue 5 (27th May 2020) - Luo, Zhe; Wu, Zhongyang; Fu, Longlong
Abstract: In this article, a simplified approach for the reliability-based design of laterally loaded drilled shafts considering the spatial variability of soil property is presented. This simplified approach utilizes a conventional reliability method implemented using the variance reduction technique. An algorithm for back-calculating the reduction factor and characteristic length for various shaft slenderness ratios is proposed. This simplified approach can yield responses for drilled shafts that are equivalent to those obtained using random field modeling (RFM), which is a far more complex process. The simplified approach does not require the knowledge of random field theory and can be an efficient design tool in geotechnical engineering practice.